Multimodal Imaging in a Patient with Traumatic Choroidal Ruptures. Issue 6 (8th November 2017) - Pierro, Luisa; Giuffrè, Chiara; Rabiolo, Alessandro; Gagliardi, Marco; Arrigo, Alessandro; Bandello, Francesco
Purpose: To describe the case and the follow-up of a traumatic choroidal rupture characterized by means of multimodal imaging including color fundus photographs, infrared reflectance, blue autofluorescence, swept-source optical coherence tomography, fluorescein angiography (FA), indocyanine green angiography (ICGA), and optical coherence tomography angiography (OCT-A). Methods: Case report. Results: A 17-year-old boy was referred to our clinic complaining of reduction in visual acuity in the right eye (RE) after a blunt ocular trauma during a soccer match. Dilated fundus examination of RE showed 2 peripapillary choroidal ruptures located temporally and inferiorly to the optic disc. Among different imaging tools useful in the diagnosis and study of choroidal ruptures, particular attention must be paid to OCT-A, which showed the lesions as breaks in the choriocapillaris plexus with a hypointense appearance due to the lack of substance. Moreover, along the break it was possible to see the projection of the underlying choroidal vasculature, which appeared hyperintense. The retinal vascular plexa were spared. Conclusions: All patients presenting with blunt ocular trauma should undergo fundus examination to exclude damage to the optic nerve, retina, and choroid, and need close follow-up to avoid the development of secondary complications such as choroidal neovascularization. Optical coherence tomography angiography might add relevant information in the global evaluation and follow-up of choroidal ruptures in a noninvasive fashion, and could replace other invasive modalities such as FA or ICGA.